Analisis Strategi Pengembangan Industri Hilir Kelapa Sawit Pada PT SMART Tbk - , Riyan Wiharjanto, Dr. Bambang Riyanto LS, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to evaluate the performance of the strategy that has been pursued by PT SMART Tbk by linking the internal and external condition of the company. In addition, strategic recommendations are also given to improve the competitiveness of enterprises.The scope of the research is qualitative case study on PT SMART Tbk. The data used in this study derived from primary and secondary data. Primary data obtained through interviews, documentation and observation. While secondary data compiled from company financial statements, internal data related to research, World Growth-Palm Oil Green Development Campaign (2011) reports, Indonesian Capital Market Directory (2011), and Agribusiness Development Prospects and Direction of Indonesian Palm Oil Volume 2 (2009) reports. There are two types of analysis used in this study, namely internal and external analysis. Internal analysis related to the analysis of marketing and distribution, production process analysis, organizational analysis and corporate governance standards, analysis of human resource development, and analysis of company financial performance. While external analyzes using several tools, such as the dominant economic factor analysis, analysis of Porter's five forces of competition, Driving Forces analysis, Analysis of Key Success Factor (KSF), and Strategic Group Maps analysis. The results showed that the integration of business strategy firm run by focusing on resource development and technology development is appropriate and effective. However, the company will be able to increase its competitiveness if it is supported by additional strategies include increased infrastructure support, community empowerment on the plantation increased plasma, and increase in investment product development-oriented derivative of alternative energy.